VALIDITAS DAN RELIABILITAS ANGKET RASA EMPATI - Ranayuda Fujiansyah Komarudin; Euis Eti Rohaeti; Wiwin Yuliani (IKIP Siliwangi, 2021)
Empathy is a person's ability to understand and place a position in accordance with the feelings of others. A student must have empathy to be more sensitive to the surrounding environment. The purpose of this study was to determine the sense of empathy in class VIII MTSN 3 Purwakarta using a questionnaire. The method in this research is to use research and development. This method is used to create a product, as well as to test the effectiveness of a product. The sample in this study was the students of class VIII at MTs Negeri Purwakarta as many as 23 students. The research instrument used was a questionnaire containing 6 tests of the characteristics of empathetic people. Analysis of the data used is testing the validity and reliability of SPSS assisted. The results of the study found that 23 statements were valid because the results of the calculation of rcount were more than rtable. The reliability test showed that Cronbach's Alpha coefficient value was 0.788 so it was declared reliable in the high category so that the questionnaire was reliable. Thus this questionnaire can be used to measure students' empathy. Keywords: Empathy, Validity, Reliability